Are choice experiments incentive compatible? A test with quality differentiated beef steaks - Lusk, J.L; Schroeder, T.C (American journal of agricultural economics, 2004)
This study compares hypothetical and nonhypothetical responses to choice experiment questions. We test for hypothetical bias in a choice experiment involving beef ribeye steaks with differing quality attributes. In general, hypothetical responses predicted higher probabilities of purchasing beef steaks than nonhypothetical responses. Thus, hypothetical choices overestimate total willingness-to-pay for beef steaks. However, marginal willingness-to-pay for a change in steak quality is, in general, not statistically different across hypothetical and actual payment settings.